Unveiling success: determinants of a successful haematopoietic stem cell transplant: a case report - Tariq Mahmood Satti; Rimsha Jafar; Habib, Zoya; Koukab Ejaz; Zulqarnain Arif; Fahad Haider Shah (Journal of the Pakistan Medical Association, 2025)
Patients with beta thalassemia major can make an uneventful and miraculous recovery after bone marrow transplantation despite lacking a sibling donor. The once widely accepted belief that only a transplant received from a sibling or mother would lead to a successful outcome has been challenged by the advent of new approaches and drugs. We present the case of a 15-year-old girl who received stem cells from her father and, despite suffering an attack of acute graft versus host disease (aGVHD) and depression, still managed to achieve a 100% success rate. This report highlights the importance of factors other than the source of stem cells in evaluating the patient’s outcome and the lack of awareness about this disease even among the literate population in our country. Keywords: Haematopoietic stem cell transplantation, Beta thalassemia, GVHD.